Testing a model of the UK by the method of indirect inference - Patrick Minford; Konstantinos Theodoridis; David Meenagh (Cardiff University, Cardiff Business School, 2007)
We use the method of indirect inference to test a full open economy model of the UK that has been in forecasting use for three decades. The test establishes, using a Wald statistic, whether the parameters of a time-series representation estimated on the actual data lie within some confidence interval of the model-implied distribution. Various forms of time-series representations that could deal with the UK's various changes of monetary regime are tried; two are retained as adequate. The model is rejected under one but marginally accepted under the other, suggesting that with some modifications it could achieve general acceptability and that the testing method is worth investigating further.
Keywords: C12; C32; 330; Bootstrap; Model Evaluation; Non-Linear Time Series Models; Indirect inference; open economy models; UK models; Bootstrap-Verfahren; Zeitreihenanalyse; Dynamisches Gleichgewicht; Ökonometrisches Makromodell; Theorie; Großbritannien